Aquaponics: A Potential Option for Urban Food Supplement in Kathmandu Valley - Khadka, Udhab Raj; Maharjan, Sanu Maiya (Tribhuvan University Journal, 2019)
Growing urbanization in Kathmandu Valley has reduced the agriculture land and is anticipated further reduction coming days leading to agricultural vulnerability. The increasing built-up areas, however, might be opportunity for alternative methods of agriculture production like aquaponics which incorporates both aquaculture and hydroponics in a single unit. This system helps to produce food (fish and vegetables), especially in the areas where the availability of cultivable land and water is scarce. This study was carried out to demonstrate the feasibility of aquaponics in Kathmandu Valley. For the experiment, two media filled aquaponic systems (MFS) covering one square meter area were set-up using hog-plum (Choerospondias axillaries) seeds (Bh) and gravels (Bg) as growing media in hydroponic and systems were named as AS-1 and AS-2, respectively. In both Bh and Bg, 11 seedlings of Indian spinach having 5 g total weight were transplanted in grow bed containing hog-plum, and 15 catfish (Clariasbatrachus) having 45 g weight were stocked in Tank-1 (T-1) of AS-1. Likewise, in AS-2 system, 5 g spinach were transplanted in grow-bed containing gravel, and 34 carp (Cyprinus sp.) fish having 34 g weight were stocked in Tank-2 (T-2) of AS-2. After 40 days, 550 g spinach was produced from the system containing hog-plum seeds as grow-bed and 1060 g spinach from the system containing gravel as grow-bed. Likewise, 45 g catfish reached 550 g in 90 days in Tank-1 (T-1) and 34 g carp reached 109 g in Tank-2 (T2). All the growth performances like specific growth rate (SGR), average daily growth (ADG), daily growth index (DGI), percent weight gain (%WG) of Indian spinach in grow-bed containing gravel (Bg) were found higher in comparison to the grow-bed containing hog-plum seed (Bh). The survival rate of catfish and carp was found to be 86.7% and 90.6%, respectively. The growth performance of Indian spinach was significantly different (p<0.05) in the two growing media. This result shows that aquaponics has potential to produce both fish and spinach simultaneously at the same unit using small space in city like Kathmandu Valley. Further detailed study is required for comparative study of fish and evaluating cost and benefit, and commercial potentiality.